Magnetic field fluctuation features at Swarm's altitude: A fractal approach. Issue 9 (7th May 2015) - De Michelis, Paola; Consolini, Giuseppe; Tozzi, Roberta
Abstract The European Space Agency's Swarm mission provides a qualitatively new level of observational geomagnetic data, which allows us to study the spatial features of magnetic field fluctuations, capturing their essential characteristics and at the same time establishing a correlation with the dynamics of the systems responsible for the fluctuations. Our study aims to characterize changes in the scaling properties of the geomagnetic field's spatial fluctuations by evaluating the local Hurst exponent and to construct maps of this index at the Swarm's altitude (∼460 km). Since a signal with a larger Hurst exponent is more regular and less erratic than a signal with a smaller one, the maps permit us to localize spatial structures characterized by different scaling properties. This study is an example of the potential of Swarm data to give new insights into ionosphere‐magnetosphere coupling; at the same time, it develops new applications where changes in statistical parameters can be used as a local indicator of overall magnetospheric‐ionospheric coupling conditions.